2023
DOI: 10.3390/tropicalmed8030146
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cortisol as a Biomarker of Severe Dengue

Abstract: Dengue infection presents a wide range of clinical symptoms. Serum cortisol is known as a severity predictor of serious infection but is not yet clearly understood in dengue infection. We aimed to investigate the pattern of cortisol response after dengue infection and evaluate the possibility of using serum cortisol as the biomarker to predict the severity of dengue infection. This prospective study was conducted in Thailand during 2018. Serum cortisol and other laboratory tests were collected at four time poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
3
0
2
Order By: Relevance
“…Chaiyaratana et al 49 showed that a serum ferritin level ≥1200 ng/mL had a high sensitivity, but a relatively low specificity to predict the occurrence of severe dengue. Bongsebandhu et al 50 showed that D-dimer was significantly associated with dengue severity. Early increasing D-dimer in the febrile stage could predict the severity of dengue infection during the initial stage of the illness, with a 68.4% positive predictive value.…”
Section: Resultsmentioning
confidence: 99%
“…Chaiyaratana et al 49 showed that a serum ferritin level ≥1200 ng/mL had a high sensitivity, but a relatively low specificity to predict the occurrence of severe dengue. Bongsebandhu et al 50 showed that D-dimer was significantly associated with dengue severity. Early increasing D-dimer in the febrile stage could predict the severity of dengue infection during the initial stage of the illness, with a 68.4% positive predictive value.…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence of cortisol changes in dengue. Patients with severe dengue seem to have increased levels of cortisol, but the exact meaning of this remains unclear 64 .…”
Section: Kidney Involvementmentioning
confidence: 99%
“…There is an ongoing debate about the use of parenteral corticosteroids in severe dengue 65 . There is a WHO guideline for dengue management 64 . Patients should be cautioned against taking anti-inflammatory drugs because of the risk of bleeding in severe thrombocytopenia 50 , 67 , 68 .…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations